THE IMPACT OF VARIOUS LIFESTYLE FACTORS ON BLOOD GLUCOSE CONTROL IN INDIVIDUALS WITH TYPE 2 DIABETES: A REVIEW OF CURRENT RESEARCH AND CLINICAL RECOMMENDATIONS - Ryszard Łagowski; Julia Kosęda; Honorata Juniewicz; Zuzanna Kudlińska; Patryk Heryć; Karolina Kananowicz; Zofia Laska; Marianna Latour; Anna Jędrasiak; Jakub Piotrowski (International Journal of Innovative Technologies in Social Science, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from peripheral insulin resistance and progressive β-cell dysfunction. The disease leads to micro- and macrovascular complications, significantly impairing patients’ quality and length of life. Lifestyle factors, such as diet, physical activity, body weight, sleep, stress, and substance use, play a key role in the pathogenesis of T2DM. Numerous studies show that modifying these factors improves glycemic control, lowers HbA1c, reduces the need for hypoglycemic medications, and in some cases may induce disease remission. Low-carbohydrate, Mediterranean, and low-calorie diets improve metabolic parameters and support weight reduction. Regular physical activity, including aerobic, resistance, and high-intensity interval training, increases glucose uptake by muscles, improves insulin sensitivity, and reduces visceral fat. Optimal body weight, waist circumference, and sleep duration and regularity significantly affect blood glucose levels and HbA1c control. A comprehensive approach addressing diet, physical activity, weight management, and sleep improvement promotes effective glycemic control and reduces the risk of T2DM complications.